Effects of Biostabilization on Engineering Properties of Geomaterials - Shengting Li; Chenyi Luo; Yi Yang; Lvzhen Yang; Lijian Wu; Tuo Huang; Zhuangji Wang (Advances in Civil Engineering)
Biostabilization is a newly proposed method to improve the strength and durability of geomaterials, and it can serve as an alternative to chemical and mechanical stabilization. The objectives of this study are to perform biostabilization treatments for selected roadway construction geomaterials and to evaluate the biostabilization effects on engineering properties of the geomaterials. Three types of geomaterials were selected, and two of them were compacted soil from unpaved road surface. Bacillus pasteurii, the biostabilization bacterium, was used to induce mineral precipitates within the geomaterial pore spaces, where the biostabilization effects were performed. Two types of liquid incubation media, containing NH4Cl or (NH4)2 SO4, were applied for bacteria culturing. Unconfined compression, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) measurements were conducted to evaluate the biostabilization results. From unconfined compression, sample strength performance was improved by the biostabilization treatments; the benefits of biostabilization were pronounced by a relatively long culturing time and an oven-dry procedure; the liquid culturing medium containing NH4Cl performed better than the medium containing (NH4)2 SO4. After biostabilization, SEM photographs provided direct evidence for the precipitates induced by bacteria within the geomaterial pore space. The precipitates either connected the adjoined particles or partially covered the particle surface, which increased the surface roughness. EDS and XRD results indicated that calcite, dolomite, and albite were the major precipitates produced during biostabilization treatments. In conclusion, biostabilization ameliorated the microstructures of the geomaterials and improved their strength. Future research topics should include the applications of biostabilization for in situ road construction.